Inclusive governance of hydropower on shared rivers? Toward an international legal geography of the Lower Mekong basin - Hensengerth, Oliver (Frontiers in Climate, 2024)
Hydropower is now the largest source of renewable energy worldwide. The International Renewable Energy Agency estimates that current hydropower capacity will need to double by 2050 in order to transition to net zero and to arrest the rise of global temperatures at 1.5 degrees Celsius. Much of the currently built and planned dams are on rivers shared between two or more countries. This raises the risk of increased inter-state conflicts. However, to exploit hydropower peacefully, the impact on local communities must also be considered. This foregrounds the need to build inclusive institutions that can mediate the different interests, norms, and values held by communities located across different scales. The article examines the role of international river basin organizations to manage this legal pluralism in shared river basins. In many basins globally, such as the Lower Mekong, the Columbia, the Zambezi, or the Senegal, international river basin organizations are tasked with the development of shared water resources. To understand to what extent river basin organizations can mediate the legal pluralism in a shared basin, the article develops an international legal geography approach to the governance of transboundary waters in an attempt to uncover marginalization and disempowerment in the process of law-making. It therefore expands the analytical scope of legal geography to the study of transnational spaces, in this case complex ecosystems for which there are no fixed jurisdictional boundaries. It then applies this approach to the case study of the Lower Mekong basin. Findings indicate that the Mekong River Commission, despite attempts to include project-affected people in decision-making, largely operates within a Westphalian framework of sovereignty to the detriment of more inclusive forms of governance. Project affected communities are largely unable to exert influence and are relegated to participation in alternative forums. These forums, or counter publics as Yong called them, are disconnected from official processes. While they give rise to marginalized voices and enable the creation of inclusive and participatory spaces, the exclusionary official decision-making processes continue to produce significant tension and conflict potential as hydropower is championed globally as a clean, climate friendly form of energy. As hydropower is set to double by 2050, inclusive participatory institutions in basins worldwide must be built to navigate complex stakeholder interests and to benefit those who are otherwise likely to lose out in net zero transitions. These findings are relevant for other shared basins, particularly across Southeast Asia, Africa and Latin America where hydropower is booming. An international approach to legal geography can foreground these hidden and marginalized voices and help identify ways to build inclusive institutions for the governance of shared resources.